2014
DOI: 10.1038/ncomms4383
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic graphene oxide sheets with controllable composition

Abstract: Graphene oxide potentially has multiple applications and is typically prepared by solutionbased chemical means. To date, the synthesis of a monolithic form of graphene oxide that is crucial to the precision assembly of graphene-based devices has not been achieved. Here we report the physical approach to produce monolithic graphene oxide sheets on copper foil using solid carbon, with tunable oxygen-to-carbon composition. Experimental and theoretical studies show that the copper foil provides an effective pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…4b ) were observed at peak positions of approximately 1584 cm −1 and 2673 cm −1 , respectively, in the spectrum of the graphene layer ( Fig. 4d ) 29 . This finding provided clear evidence that, even after the growth of n-GaN NRs on the monolayer graphene, the physical existence and material properties of the graphene layer were not affected and the graphene layer was not damaged or impaired.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…4b ) were observed at peak positions of approximately 1584 cm −1 and 2673 cm −1 , respectively, in the spectrum of the graphene layer ( Fig. 4d ) 29 . This finding provided clear evidence that, even after the growth of n-GaN NRs on the monolayer graphene, the physical existence and material properties of the graphene layer were not affected and the graphene layer was not damaged or impaired.…”
Section: Resultsmentioning
confidence: 89%
“…In this study, Raman spectroscopy revealed further improvement in the quality and uniformity of the monolayer graphene (with a peak intensity ratio I G /I 2D ≈ 0.38) grown using the CVD process and then transferred to a Si (111) substrate. To our knowledge, this study represents the finest graphene layer transferred directly to a Si substrate reported thus far 29 30 . The electrical properties of the graphene films that were transferred onto Si substrates were evaluated using the circular transfer length method (CTLM) structure, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Cu is well known to be a potent catalyst for the formation of graphene . Due to the presence of steam in the gas and therefore a rather high oxygen potential of the gas, the formation of graphene oxide may even be plausible . In any case, such a layer may then block the copper surface for the adsorption of C 2 H 4 and thus inhibit the formation of coke from C 2 H 4 .…”
Section: Discussionmentioning
confidence: 99%